2019
DOI: 10.1186/s12891-019-2800-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between sagittal balance and adjacent segment degeneration in anterior cervical surgery: a systematic review and meta-analysis

Abstract: Background ASD is a relatively common degenerative alteration after cervical surgery which occurs above or below the fused segment. In addition, some patients may need reoperation to treat severe ASD after the primary surgery. It was considered that sagittal balance is correlated with postoperative clinical outcomes; however, few studies have reported the influence of sagittal balance on ASD. The present study is designed to investigate whether sagittal balance impacts the pathology of adjacent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 42 publications
4
18
1
Order By: Relevance
“…This may have been caused by compensation of the unoper-ated segments, which warrants further evaluation. 29,30 Although the pseudarthrosis and subsidence rates of this study are higher than generally thought, recent reports have demonstrated that the pseudarthrosis rate after ACDF could have been underestimated, with the incidence reaching 13.0% to 22.6% for one-level operation and 45.5% to 47.0% for three-level operation. [31][32][33] The subsidence rate could have been detected with increased sensitivity since subsidence was assessed using multiple CT images.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…This may have been caused by compensation of the unoper-ated segments, which warrants further evaluation. 29,30 Although the pseudarthrosis and subsidence rates of this study are higher than generally thought, recent reports have demonstrated that the pseudarthrosis rate after ACDF could have been underestimated, with the incidence reaching 13.0% to 22.6% for one-level operation and 45.5% to 47.0% for three-level operation. [31][32][33] The subsidence rate could have been detected with increased sensitivity since subsidence was assessed using multiple CT images.…”
Section: Discussioncontrasting
confidence: 55%
“…This may have been caused by compensation of the unoper-ated segments, which warrants further evaluation. 29,30…”
Section: Discussionmentioning
confidence: 99%
“…In addition, for every 1° increase in the postoperative CL, there was an 8% reduction in the risk of complications when ASD and HO were considered together. Our results were consistent with those in the previous meta-analysis by Zhang et al, 11 who reviewed five studies and found that the postoperative degree of CL was significantly lower in patients who underwent anterior cervical spine surgery and developed ASD compared with those who did not develop ASD by the last follow-up. Based on our findings and those of previous studies, we believe that it is important to maintain normal cervical alignment after Prestige-LP CDR.…”
Section: Discussionsupporting
confidence: 93%
“…Multiple studies have shown that there is a relationship between cervical sagittal balance and neck pain, cervical disc degeneration, and the outcomes of ACDF. 3,4,7,[9][10][11][12]21,26 However, the importance of cervical sagittal parameters in CDR is rarely noted. In addition, the cervical sagittal alignment and its impacts on clinical outcomes after Prestige-LP CDR has been rarely studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation